A Qualitative Analysis of Adventurous Activities Among OEF/OIF Veterans. (2nd October 2017) - Betthauser, Lisa M.; Allen, Elizabeth; Grigsby, Jim; Brenner, Lisa A.
ABSTRACT: Semistructured interviews qualitatively explored Operation Enduring Freedom/Operation Iraqi Freedom veterans' experience of activities that provide a rush or thrill, reasons for/against engaging in such activities, and affect experienced during these activities. Phenomenological methods were used to analyze the data. Veterans engaged in activities for a sense of accomplishment, mood alteration, fitness, and bonding. Veterans described internal and external barriers for engagement in such activities. Impact of combat on the frequency of activity engagement was also discussed. Clinical implications support the notion that as veterans adapt to civilian life, they may benefit from engagement in safe, affordable, and exciting leisure activities.